The construction of diverse nitrogen-containing heterocycles via the reaction of amines or azides with metallocarbenes - Bott, Tina (My University, 2011)
A fundamental goal in organic chemistry is the development of new and innovative ways of transforming simple building blocks into complex structures. The formation of ylides from the reaction of metallocarbenes with heteroatoms, such as the nitrogen of an amine or azide, is an example of a versatile methodology that is capable of undergoing divergent transformations into a wide variety of nitrogen-containing heterocycles. Azetidines are a class of small, strained amines, which display properties of their smaller and larger ring counterparts, aziridines or pyrrolidines, depending on the nature of their substitution pattern and their chemical environment. Chapter 1 will highlight the recent advances in the synthesis and application of these molecules in the recent literature. In chapter 2, we demonstrate the ability of azetidines to undergo ring expansion to pyrrolidines via the Stevens rearrangement of ammonium ylides. In this methodology, azetidines behave in a manner distinct from equivalent systems lacking ring strain. This investigation allowed for the construction of a range of differently functionalized pyrrolidines in a one step procedure from readily available azetidines and diazocarbonyl compounds. An extension of this successful azetidine ring expansion chemistry, to provide access to more complex heterocyclic ring systems, is described in chapter 3. The goal of this project was to determine the functionality required on the azetidine ring to direct the Stevens rearrangement in an intramolecular fashion. The use of carbonyl and silyl groups as a means of directing the transformation was investigated. These groups were chosen for their ability to be easily removed or transformed after the ring expansion process in order to access a broader range of compounds during later applications. In chapter 4, we describe a new methodology for the formation of C-acylimines through the reaction of organic azides with in situ generated metallocarbenes. Using aryl-tethered diazo-azide substrates allowed for the production of highly reactive C-acylimines, which in the presence of carbon nucleophiles could be subsequently trapped to form highly conjugated indolone derivatives. In contrast, when an alkyl tether was used, we observed the formation of an isolable C-acylimine, which displayed intriguing umpolung chemistry when treated with organozinc reagents.
Keywords: azetidines; Stevens; azides; heterocycles